Dissertation - Tran, Lan Phuong (2015)
At first I would like to say my sincerest thank to my classmates, and teachers - professors of the University of Nottingham. Especially, I wish to express my heartfelt gratitude to my Supervisor Dr. Richard Simper for his valuable guidance, enthusiastic supports, and dedicated supervision as well as the inspiration and motivation. Furthermore, I want to send my thankful gratitude to my sister, Lily Tran, my best friends Khanh Chi Nguyen, Aroosha and Adam Nguyen for staying next to me in difficulties. Finally, I would love to say a gratefully thank to my family, especially Mom and Dad who always behind me to motivate and support.